Genetic Diversity of an Imperiled Neotropical Catfish and Recommendations for Its Restoration - Fonseca, Fernando S.; Domingues, Rodrigo R.; Hallerman, Eric M.; Hilsdorf, Alexandre W. S. (Frontiers in Genetics, 2017)
The long-whiskered catfish Steindachneridion parahybae (Family Pimelodidae) is endemic to the Paraíba do Sul River basin in southeastern Brazil. This species was heavily exploited by artisanal fisheries and faces challenges posed by dams, introduced species, and deterioration of critical habitat. The remaining populations are small and extirpated from some locales, and the species is listed as critically endangered in Brazil. Screening variation at a partial mitochondrial control region sequence (mtCR) and 20 microsatellite loci, we: (i) describe the patterns of genetic diversity along its current distributional range; (ii) test the null hypothesis of panmixia; (iii) investigate the main factors driving its current population structure, and (iv) propose management of broodstock for fostering recovery of wild populations through genetically cognizant restocking. Our microsatellite data for 70 individuals from five collections indicate moderate levels of heterozygosity (HO = 0.45) and low levels of inbreeding (FIS = 0.016). Individual-based cluster analyses showed clear genetic structure, with three clusters of individuals over the collection area with no mis-assigned individuals, suggesting no recent migration among the three clusters. Pairwise DEST values showed moderate and significant genetic differentiation among all populations so identified. The MUR population may have suffered a recent demographic reduction. Mitochondrial control region sequences for 70 individuals exhibited 36 haplotypes resulting from 38 polymorphic sites. Overall, mitochondrial haplotype diversity was 0.930 (± 0.023) and nucleotide diversity was 0.011 (± 0.002). Significant population structure was observed, with ST = 0.226. Genetic markers could be used in a hatchery-based restoration program emphasizing breeding of pairs with low kinship values in order to promote retention of genetic diversity and avoid inbreeding. Individual average kinship relationships showed 87.3% advised matings, 11.0% marginal matings, and 1.7% advised against. While these results comprise a contribution towards planning better breeding management and monitoring, parallel actions to be undertaken include surveying healthy riverine habits for reintroduction and continued searching for wild individuals to introduce new variation into the captive broodstock to avoid adaptation to captivity and to minimize inbreeding.